PENGARUH KOSAKATA MAHASISWA TERHADAP NILAI READING COMPREHENSION TOEFL (STUDI KORELASIONAL KUANTITATIF) - Muliasari, Dewi (ITB AAS Indonesia Surakarta, 2025)
This study aims to investigate the influence of vocabulary size on students' ability to comprehend TOEFL Reading Comprehension texts among Accounting students at Institut Teknologi Bisnis AAS Indonesia. A quantitative method with a correlational approach was employed in this research. The sample consisted of 40 students selected through purposive sampling. Data were collected using two instruments: the Vocabulary Size Test (VST) to measure students' vocabulary knowledge and the Reading Comprehension scores from the TOEFL Prediction Test to assess their reading comprehension ability. The data were analyzed using the Pearson Product Moment correlation test, which revealed a positive and significant relationship between vocabulary size and TOEFL Reading Comprehension scores, with a correlation coefficient of 0.613 and a significance level of 0.000 (p < 0.05). These findings indicate that students with a larger vocabulary size tend to achieve higher performance in understanding academic English texts. This research provides practical implications for developing English learning strategies, particularly vocabulary enhancement programs to help students achieve optimal results in TOEFL tests. Keywords: Vocabulary Size, Reading Comprehension, TOEFL, Accounting Students, Correlation.